TEACHER-MADE SPEAKING ACHIEVEMENT TEST - Khairuddin Khairuddin (INOVISH JOURNAL, 2018)
One of the main jobs of an English teacher teaching speaking skill is to develop and administer a speaking test in order to measure how much or little the students have achieved the instructional objectives and materials upon completion of a language program. Through the test results, the teacher is enabled to make decisions such as deciding the effectiveness of the language program and passing or advancing the students to the next level of the program.To qualify herself in developing a valid and realiable speaking test, both conceptual and practical knowledges are needed. The article presents the needed knowledge about speaking test covering the concepts ofÂ  speaking skill construct, criterion-referenced test, analytic approach, criteria setup, and scoring and grading. The article also reports the implementation of the teaher-made speaking test to testing the speaking skills achievement of the students in Politeknik Kesehatan Kemenkes Malang. Key words: speaking test, achievement test, criterion-referenced test, analytic approach, scoring, grading